The “Swing-Door” Regrafting of Donor Site: An Alternative Method for Split-Thickness Skin Graft in the Hand - Kim, Jin Soo; Park, Chan Ju; Koh, Sung Hoon; Lee, Dong Chul; Roh, Si Young; Lee, Kyung Jin (Archives of Plastic Surgery, 2024)
Background Skin defects in the hands are common injuries, and autologous skin grafting is the ideal treatment. However, complications can occur at the donor and recipient sites. This study compares the “Swing-door” technique with conventional skin grafting.Methods From August 2019 to February 2023, 19 patients with skin defects of hand underwent the “Swing-door” split-thickness skin graft (STSG) technique. The thin epithelial layer was elevated with proximal part attached. Skin graft was harvested beneath. Donor site was then closed with epithelial flap like a “Swing-door”. The outcomes were evaluated in terms of healing time, scar formation, and pain at the donor and recipient sites. The data were compared with the conventional STSG.Results The “Swing-door” group had lower graft take percentages, but complications did not significantly differ between the two groups. The “Swing-door” technique resulted in better cosmetic outcomes, as evidenced by lower Vancouver Scar Scale scores, faster donor site epithelialization, and reduced pain and discomfort during the early postoperative period, as measured by Visual Analog Scale.Conclusion The “Swing-door” STSG is a useful alternative for treating hand skin defects.
Keywords: hand injury; wound healing; skin transplantation; hand